Simplified injury severity scale for developing countries. (7th October 2012) - Verma, Pramod Kumar
Abstract : Background: Incidence of injury widely varies because researcher uses own criteria for including minor/major injury. AIS is not applicable among community/without diagnosis. Objective: To prepare Simplified Injury Severity Scale (SISS) Methods: Various severity-related physiological and anatomical variables included and graded according to its effect on severity of injury. Simplified Injury Severity Scale (SISS): Age of the injured victim: 0–5 year(1), 6–25 years(2), 26–50 years(3), >50 years(4). Part of the body injured: Limbs(1), Abdomen/Pelvis(3), Thorax/Chest(4), Head/ Neck/ multiple/ whole body(5). Type of Injury: Superficial(4), Deep(8). Level of consciousness after injury: Normal(0), dizziness(4), Drowsiness(8), Unconscious(10). Duration of deterioration of consciousness: Momentary(2), <1 h (4), 1–24 h(8), >24 h (10). Amount of bleeding after injury/type of treatment/ systolic BP: Minimum bleeding without I/V fluid or>100(0), Moderate bleeding with I/V fluid or 100 to 80(4), Severe bleeding with transfusion or <80(8). No. of days of hospitalisation/work affected: Nil(0), <1 day(2), 1–3 days(4), 4–7 days(6), 8–15 days(8), 16–30 days(10), >30(12) Type of treatment availed: Nil(0), Outdoor(2), Indoor(4), Major operation(6), Intensive ward(8). Outcome after treatment: Normal(0), scarring(2), Disfigurement(4), Disability not affect routine work(6), Disability affect routine work(8), Incapable(10). Total scoring for injury severity: No Injury(<10), Minor Injury(10–20), Moderate(20–35), Severe(35–50), Critical(50–60), Maximum Injury(>60). Results: Community based study shows 18% no injury, 41% minor injury, 32% moderate injury, 8% severe injury, 0.5% critical injury and 0.5% maximum injury. 185 injured victims in hospital show 2.7% minor injury, 8.6% moderate injury, 34.6% severe injury, 41.1% critical injury and 13% maximum injury. Significance: This is very useful in developing countries with the advantage of it being simple, specific and effective.